Gerakan Penguatan Karakter Religius Anak di Lingkungan Tempat Pendidikan Al-Qur’an Raudatussalam Desa Sungai Teras Dalam - Muhammad Hendri Yanova; Muhammad Iqbal Ansari; Anisa Wulandari; Muhammad Naufal Ridha Ashsofi; Salma Kumala Dewi; Mohammad Sofyan Sauri (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Strengthening religious character in elementary school-aged children is a fundamental aspect in shaping their personality, morals, and social attitudes from an early age. This community service program aims to share knowledge and implement methods for strengthening religious character in students at the Raudatussalam Kindergarten (TPA) and identify supporting factors and obstacles encountered in its implementation. The results of the activity indicate that strengthening religious character in the Raudatussalam Kindergarten is implemented through the inculcation of religious values ??in daily school activities, teachers' exemplary religious behavior, and the integration of religious values ??into the learning process and non-academic activities. Key supporting factors include educator commitment, a conducive TPA environment, and parental involvement in student character development. Obstacles identified include limited learning time and differences in students' religious backgrounds. In this implementation process, strengthening religious character can be effective if it is carried out consistently and integrated between the school, family, and social environment.